1992
DOI: 10.1172/jci115801
|View full text |Cite
|
Sign up to set email alerts
|

Serological cross-reactivity between a human Ro/SS-A autoantigen (calreticulin) and the lambda Ral-1 antigen of Onchocerca volvulus.

Abstract: We have cloned and sequenced a 46-kD Ro

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

1995
1995
2014
2014

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 20 publications
2
9
0
Order By: Relevance
“…ELISA studies revealed that anti-CRT autoantibodies were directed against the N-terminal fragment. This supports the previous studies in which native Wil-2 cell CRT was proteolytically cleaved into a 23-kD N-terminal and 37-kD C-terminal fragment, of which the N-terminal fragment was found to be autoantigenic [27]. Synthetic peptides corresponding to amino acids 7-24 of human CRT have also been found to react specifically with anti-Ro/SS-A sera in ELISA [20].…”
Section: C1q-calreticulin Interaction In Sle 187supporting
confidence: 89%
“…ELISA studies revealed that anti-CRT autoantibodies were directed against the N-terminal fragment. This supports the previous studies in which native Wil-2 cell CRT was proteolytically cleaved into a 23-kD N-terminal and 37-kD C-terminal fragment, of which the N-terminal fragment was found to be autoantigenic [27]. Synthetic peptides corresponding to amino acids 7-24 of human CRT have also been found to react specifically with anti-Ro/SS-A sera in ELISA [20].…”
Section: C1q-calreticulin Interaction In Sle 187supporting
confidence: 89%
“…15 In Leishmania and Schistosoma species, the Ca 2+ binding property of CR is conserved in vitro. 16 There also is evidence concerning immunogenicity of CR from parasites in humans; anti-CR antibodies have been detected in serum from patients with onchocercosis, 17 schistosomiasis, 18 and tripanosomiasis. 19 Our results suggest the presence of a CR-like molecule in E. histolytica that appears highly immunogenic in patients with invasive amebiasis.…”
Section: Discussionmentioning
confidence: 99%
“…These include the filarial parasite and causative agent of river blindness Onchocerca [52], the blood fluke Schistosoma [53], the malarial parasite Plasmodium [54] and the trypanosome Leishmanania [2]. Two independent groups showed that autoantibody reactivity against the onchocercal calreticulin homologue (RAL-1) was significantly higher in O. volvulus-infected individuals than in endemic controls [55,56], suggesting that autoantibody reactivity against calreticulin and other autoantigens was intercorrelated as part of an onchocerciasis-associated autoimmune response. The recognition of RAL-1 by the host immune system suggests that it may be secreted by the parasite, which is plausible since the protein lacks an ER retention signal.…”
Section: Calreticulin and Protein Homology To Parasitic Proteins And mentioning
confidence: 99%